Pengaruh Doping Ca dan K pada γ-Al2O3 terhadap Sifat Fisik Katalis pada Transesterifikasi Minyak Kelapa - Eko Supriadi; Danawati Hadi Prajitno; Mahfud Mahfud; Ngatijo Ngatijo; Rahmat Basuki (REACTOR: Journal of Research on Chemistry and Engineering, 2021)
Metal doping plays important role in increasing catalytic activity of catalyst materials. In this work, Ca and K were doped to the γ-Al2O3 by dry impregnation method to study the crystallinity, surface area, activation energy, and yield in the coconut oil transesterification reaction. The success of doping was shown in the characterization of Ca/γ-Al2O3 and K/γ-Al2O3 using X-Ray Diffraction (XRD) which increasing in crystallinity from 62.2% (γ-Al2O3) to 69.3 (K/γ-Al2O3) and 76.0 (Ca/γ-Al2O3). The emerging peak of 2θ characteristics of K (29.70° and 32.65°) and Ca (25.35°, 26.77°, and 27.17°) on the γ-Al2O3 (37.66°, 45.82° and 67.22 °) was also observed. Characterization by the Surface Area Analyzer (SAA) shows that the K/γ-Al2O3 catalyst has a smaller surface area (34.03 m2/g) than Ca/γ-Al2O3 (83.77 m2/g), but a higher pore diameter (66.12 Å) than Ca/γ-Al2O3 (35.22 Å). The K/γ-Al2O3 catalyst produced greater FAME yield (93.19%) than Ca/γ-Al2O3 (29.76%) at a catalyst concentration of 2.5%, reaction time 150 s, and ultrasonic frequency of 40 kHz. The quality of the FAME catalyzed by K/γ-Al2O3 fulfills four test parameters: density, kinematic viscosity, flash point, and pour point according to SNI 04-7182-2006 standards.